Network Strategies and Performance of Canadian Investment Banks - Shipilov, Andrew V. (Academy of Management Journal, 2006)
What implications does a firm's specialization have for the performance the firm achieves by spanning structural holes between its partners? By analyzing networks within the Canadian investment banking industry, I found that, in networks rich in structural holes, both specialists and generalists performed better than banks of moderate specialization levels, and that generalist banks, in turn, performed better than specialists.